Assessing the potential of land use and land cover changes on the genetic diversity of goitered gazelle (Gazella subgutturosa) in the southern slopes of the Alborz Mountain range, Iran - Mojgan Asadollahi; Mostafa Keshtkar; Faraham Ahmadzadeh (Environmental and Sustainability Indicators)
The goitered gazelle (Gazella subgutturosa), historically widespread across the Middle East and Central Asia, is now facing a critical threat due to habitat fragmentation and population decline, particularly in Iran. To better understand the reason for the low genetic diversity of goitered gazelle populations, we combined a genetic analysis (cytb gene) like genetic diversity and demographic history using non-invasive sampling techniques with a land use/land cover study by land use dynamic degree models (LUDD) and landscape change process analysis. The selection study area is based on several populations of goitered gazelle that are located on the southern slope of the Alborz Mountain range in Iran. The results showed an alarming paucity of nucleotide diversity (0.0019) within these populations. At the same time, analysis of land use and land cover changes in the same area showed that over the past 30 years (1990–2020) urban areas have had the most increase among other land use classes (growth rate: 171%). The knowledge acquired from this research not only contributes to our understanding of the genetic makeup of goitered gazelle populations but also underscores the importance of addressing land use changes and their consequences on biodiversity. These findings emphasize the need for targeted conservation efforts to counteract the effects of urban growth on goitered gazelle habitats. Such strategies are crucial for securing the future of these populations in the southern slopes of the Alborz Mountain range and similar regions facing similar pressures.